(untitled) (Progressive Agriculture, 2015)
This research was conducted to study the effect of salting method on salt concentration in Dhaka cheese. Dhaka cheese was made in the laboratory on pilot scale and salted either by dry salting, or salt stuffing, or brining, or their combinations. Two levels of dry salting was applied, 1% and 2%, w/w. The use of different salting method had a significant (P<0.001 to 0.05) influence on salt concentration, and distribution of salt between rind and core. Brined cheeses appeared attain a quick salt equilibrium as compared to other methods. Increasing salt content from 1 to 2% (w/w) increased the salt concentration (P <0.001). Combination of 2% (w/w) salt stuffing and brining showed significantly better (P <0.001) distribution of salt followed by only brining. Progressive Agriculture 26:79-84, 2015